Desenvolvimento e caracterização de placas aglomeradas de resíduos de polieuretano "skin", com diferentes retardantes de chama - Machado, Aguinaldo Oliveira (My University, 2018)
The polymeric materials are widely used in many application areas, such as in civil construction, automotive, packaging, general industry, among others, replacing metals, ceramics and wood in a versatile and efficient way However, there is a large volume of discard of polymeric industrial waste that does not currently receive adequate destination for recycling, among them thermo-rigid polyurethane (PU) (rigid and flexible foams). The polyurethane (PU) is a versatile material because of its wide range of applications, but large volumes of PU in the form of industrial waste and post-use materials are disposed of in industrial and sanitary landfills every year. The reuse of PU waste by the mechanical recycling process is an environmentally sustainable and correct alternative, as it generates added value to this material and promotes a better use of non-renewable natural resources. The objective of this work was the development of agglomerated boards of skin polyurethane (PUs) (industrial wast) with the addition of different flame retardants, as well as the evaluation of fire reaction, morphological, physical and mechanical properties of the agglomerates obtained. The compositions used were 40 to 70 % (mass) industrial waste PUs, 30 % binder agent (Elastan) and 0 to 30 % of different flame retardants (alumina trihydrate - ATH, melamine polyphosphate - MPP, ammonium polyphosphate - APP and antimony trioxide + decabromodiphenyl oxide - TADB). To obtain the agglomerated boards, different compositions were compression molded using 2 to 6 kgf·cm-2 at 60 °C for 10 min. This study concluded that the samples PUs(40)/APP(30) and PUs(40)/TADB(30) (containing 30 % by mass of flame retardants) presented the best results of reaction to fire, with classification V0, according to the UL94-V standard. It was also evidenced that different size of PU granulometry does not alter the properties of reaction to fire of the developed agglomerates. The mechanical tests show that the agglomerates have superior resistance than necessary for the handling and application, and the results of thermal conductivity prove that these materials can possibly be destined for thermic applications in building construction and industry.
Os materiais poliméricos são vastamente utilizados em várias áreas de aplicação, como na construção civil, automobilística, embalagens, indústrias em geral, entre outras, substituindo de modo versátil e eficiente os metais, cerâmicos e madeira. No entanto, existe um grande volume de descarte de resíduos industriais poliméricos que atualmente não recebem destinação adequada para reciclagem, entre eles o poliuretano (PU) termorrígido (espumas rígidas e flexíveis). O PU é um material versátil devido a sua vasta possibilidade de aplicações, porém grandes volumes de PU na forma de resíduos industriais e materiais de pós-uso são descartados em aterros industriais e sanitários todos os anos. O reaproveitamento dos resíduos de PU pelo processo de reciclagem mecânica é uma alternativa ambientalmente sustentável e correta, pois gera valor agregado a este material e promove uma melhor utilização dos recursos naturais não renováveis. O objetivo deste trabalho foi o desenvolvimento de placas aglomeradas de resíduos industriais de poliuretano skin (PUs) com a adição de diferentes retardantes de chama, além da avaliação das propriedades de reação ao fogo, morfológicas, físicas e mecânicas dos aglomerados obtidos. As composições utilizadas foram 40 a 70 % (massa) de resíduos industriais de PUs, 30 % de agente aglomerante (Elastan) e 0 a 30 % de diferentes retardantes de chama (alumina trihidratada - ATH, polifosfato de melamina - MPP, polifosfato de amônio - APP e trióxido de antimônio + óxido de decabromodifenila - TADB ). Para obtenção das placas aglomeradas, diferentes composições foram moldadas por compressão utilizando 2 a 6 kgf·cm-2 a 60 ºC por 10 min. Este estudo concluiu que as amostras PUs(40)/APP(30) e PUs(40)/TADB(30) (contendo 30 % (massa) de retardantes de chama) apresentaram os melhores resultados de reação ao fogo, com classificação V0 conforme a norma UL94-V. Foi evidenciado também que diferentes tamanhos de granulometrias de PUs não alteraram as propriedades de comportamento ao fogo dos aglomerados desenvolvidos. Os ensaios mecânicos mostraram que os aglomerados possuem resistência superior à necessária para o manuseio e aplicação dos mesmos, e os resultados de condutividade térmica mostraram que estes materiais possivelmente podem ser destinados para aplicações térmicas na construção civil e na indústria.
Keywords: Poliuretano; Resíduos; Calor - Condução; Polyurethanes; Waste products; Heat - Conduction